Should we be concerned about incomplete taxon sampling when assessing the evolutionary history of regional biotas?. (7th June 2021) - Molina‐Venegas, Rafael; Lima, Herlander
Abstract: Region‐specific phylogenies are increasingly used in biogeography and macroecology. However, there is debate as to whether incomplete taxon sampling inherent in these phylogenies can bias divergence time estimations. Here, we draw on a global genus‐level plant phylogeny and 345 regional phylogenies derived from the global tree to fill in this gap of knowledge. Genus ages as obtained from the regional phylogenies were significantly older than those extracted from the global tree across all regions, yet the correlation between both types of ages was overall high, particularly in taxon‐rich regions. Thus, comparing divergence time estimates from taxon‐rich regional phylogenies within regions and in a relative manner seems reasonable. However, comparisons among regional biotas could be misleading if taxon ages are inferred from their respective regional phylogenies because differences in divergence times between the biotas may appear greater than they are regardless of taxon richness.